Functions of patient- and family-centered pediatric cancer communication in Pakistan - Graetz, Dylan E.; Ahmad, Alia; Raza, Muhammad Rafie; Hameed, Ambreen; Naheed, Asma; Najmi, Atoofa; Quanita, Afia tul; Munir, Shabnam; Ahmad, Safwan; Ferrara, Gia; Staples, Courtney; Rodriguez Galindo, Carlos; et al. (Frontiers in Oncology, 2024)
BackgroundCommunication is an essential aspect of high-quality patient- and family-centered care. A model for pediatric cancer communication developed in the United States defined eight communication functions. The purpose of this study was to explore the relevance of these functions in Pakistan as part of an effort to understand the role of culture in communication.Materials and methodsSemi-structured interviews were conducted with 20 clinicians and 18 caregivers of children with cancer at two major cancer centers. Interviews were conducted in Urdu or English and transcribed and translated as necessary. Two independent coders used a priori codes related to the communication model as well as novel codes derived inductively. Thematic analysis focused on operationalization of the functional communication model.ResultsClinicians and caregivers in Pakistan discussed the importance of all eight communication functions previously identified including: information exchange, decision-making, managing uncertainty, enabling family self-management, responding to emotions, supporting hope, providing validation, and building relationships. The operationalization of these functions was influenced by Pakistani cultural context. For example, information-exchange included the importance of addressing preconceptions and community myths, while managing uncertainty included strong references to religion and faith-based coping. Essential to all eight functions was trust between the family and the medical team.DiscussionThese findings support the use of this functional communication model in diverse pediatric oncology settings and emphasize the importance of trust. Culturally sensitive operationalization of these functions could inform the adaptation of tools to measure communication and interventions aimed at supporting the needs of parents of children with cancer.